Shift duty and cognitive alertness (2023)
Night shift, a typical shift work common to 24-hour production companies is identified with a number of after-effects on health of workers, ranging from physical to psychological. Lack of solutions to these effects could result in cognitive deficiencies for workers and increased downtime for organisations. Therefore, to overcome the problems associated with shift work, especially night shift, there is the need to understudy the cognitive alertness of workers, in relation to shift duty. This chapter discusses the meaning, history, and forms of shift work, compares and classifies shift work types, highlights the merits and demerits of shift work, dwells on cognitive effects, cognition and cognitive ability, as well as factors affecting cognition and methods of testing cognitive ability. It also covers the Wechsler's classification of intelligence, circadian rhythm, night shift and cognition, together with suggested solutions. Lastly, it finally draws conclusions from the areas covered.